INSPECTION AND MAINTENANCE OF LAND DAMS: A PRACTICAL STUDY - Euflauzino de Paula, Antônio; Borges de Medeiros, Leandro; Barbosa de Freitas Filho, Fernando; Corrêa Veloso dos Santos, Felipe (Journal of Interdisciplinary Debates, 2024)
Periodic inspection of dams is vital to ensure safety and minimize environmental and social risks. This study focused on the inspection techniques for earth dams at the Residencial Condominio Area in Goiânia, Goiás, addressing methods such as visual inspection, as well as advanced technologies. Significant issues were identified in dams 01 and 02, including excessive vegetation, coastal erosion, sedimentation, and deterioration of the impermeable membrane, which affect stability and water quality. The study recommends corrective actions such as tree pruning, vegetation control, and repairs to the impermeable membrane, emphasizing the importance of regular maintenance to protect communities and the environment. Another point of observation found in this work is the precariousness of safety and protection barriers for people and animals that live in their neighborhoods.